1995
DOI: 10.1007/bf01857661
|View full text |Cite
|
Sign up to set email alerts
|

Cancer awareness and self-examination practices in young men and women

Abstract: Participants in this study (N = 178) were poorly informed about risk factors, warning signs, and self-examination (SE) practices for two common cancers in young adults, testicular cancer in men and breast cancer in women. Compared to women, men were less likely to know about, see the importance of, or practice SE. We found no relationship between internal locus of control, hypochondriasis, and loneliness, on the one hand, and cancer knowledge and SE, on the other. The best predictors of cancer awareness and SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 23 publications
4
69
0
3
Order By: Relevance
“…The levels identified are also consistent with those reported by Katz et al (1995) in their recent study based on US data. In contrast, the results are remarkably higher than those reported in earlier studies (Cummings, 1983;Neef, 1991;Reno, 1988;Thornhill, 1986), suggesting that perhaps there has been an increase in awareness and practice of testicular self-examination in young men over the last decade.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The levels identified are also consistent with those reported by Katz et al (1995) in their recent study based on US data. In contrast, the results are remarkably higher than those reported in earlier studies (Cummings, 1983;Neef, 1991;Reno, 1988;Thornhill, 1986), suggesting that perhaps there has been an increase in awareness and practice of testicular self-examination in young men over the last decade.…”
Section: Discussionsupporting
confidence: 90%
“…However, as the self-efficacy scale had low reliability, this prediction should be viewed with caution. Furthermore, the studies conducted by Brubaker and Wickersham (1990) and Katz et al (1995) also identified self-efficacy as a significant predictor of TSE performance.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The TCKS is a 10-item scale (range of scores ϭ 0 -10 determined by the sum of questions answered correctly) based on an instrument developed by Katz and colleagues to assess TC-related knowledge among young adults (Cronbach's alpha ϭ 0.70). 39 It included items regarding TC etiology, the timing and method of testicular self-examination (TSE) and the sequelae of TC.…”
Section: Knowledgementioning
confidence: 99%